Rapid fulfillment of online orders in omnichannel grocery retailing - Christian Dethlefs; Manuel Ostermeier; Alexander Hübner (EURO Journal on Transportation and Logistics (EJTL), 2022)
stablishing innovative fulfillment options for online orders has become a key challenge for bricks-and-mortar retailers. A mere focus on store sales is no longer affordable due to the competition by pure online players. Retailers are continuously developing new approaches for online order fulfillment and last-mile logistics. Further shortening lead times is becoming even more important in this context. One recently developed concept is the omnichannel approach where existing structures are utilized and distribution centers (DCs) and local stores are integrated into a holistic fulfillment concept. This concept is especially relevant when retailers are providing fast delivery services (e.g., same-hour delivery). It resembles a multi-depot vehicle routing problem where all facilities act as depots and orders are assigned based on processing and transportation costs as well as available delivery capacity. We address this new concept and present the novel problem for rapid integrated order fulfillment in grocery retailing. We empirically identify decision-relevant costs for order processing in stores and develop an approach for the evaluation of overall fulfillment costs. Our work considers the order assignment to heterogeneous depots and vehicle routing for each depot depending on depot-specific fulfillment costs using a tailored cluster-first-route-second heuristic. We show that integrated rapid order fulfillment can reduce costs by an average of 7.4% compared to order fulfillment from DCs. However, as order processing costs in stores remain a significant cost factor, DCs will always have some relevance and cannot entirely be replaced by delivery from stores. Our results highlight the importance of modeling order processing costs in stores for actual order fulfillment decisions in a heterogeneous network.
Keywords: 330; Grocery retailing; Multi-depotIntegrated rapid order fulfillment; Vehicle routing; Same-day delivery